Read or skip privacy policies when installing apps on wearable devices: the roles of perceived necessity and threat clues - Yu Pan; Yiyin Ruan; Mengyi Chang; Dong Lyu; Yuhao Li (Humanities & Social Sciences Communications, 2024)
Abstract Wearable devices are increasingly integral to our daily lives but raise significant concerns about the security of personal data. In contrast, users often skip reading privacy policies when installing apps on wearable devices. This gap between the concerns and behaviors has spurred disputes regarding business ethics between app providers and users when private information is leaked. While much research has explored the reasons underlying users’ skipping behaviors on mobile phones or tablets, there has been limited attention given to wearable devices despite their prevalence. Unlike mobile phones or tablets, wearable devices often have limited capabilities, necessitating users to install essential apps and perceive a strong sense of necessity. This research, using both eye tracking and self-report methods, investigates how this perceived necessity affects users’ attention to privacy policies on wearable devices during app installations and how it interacts with the presence of threat clues – a key factor that influences behaviors toward privacy policies. In Study 1, eye tracking technology is applied to observe the variation in users’ attention toward privacy policies. Results indicate that when users perceive a high (vs. low) necessity for an app, they pay less attention to its privacy policy. This effect is amplified when there are strong threat clues present. In Study 2, based on the process-dissociation procedure (PDP), the cognitive mechanisms underlying user reading behavior are uncovered. The findings show that users with high perceived necessity are less inclined to engage in analytical processing when reading privacy policies, and this tendency is further strengthened by strong threat clues. This research supplements the existing literature on users’ behaviors toward privacy policies on wearable devices, and it also provides practical insights for prompting users to pay more attention to privacy policies and enjoy a secure digital experience.